Egg performance, egg quality, and nutrient utilization in laying hens fed diets with different levels of rapeseed expeller cake - Swiatkiewicz, Sylwester; Koreleski, Jerzy; Arczewska-Wlosek, Anna (MTT Agrifood Research Finland, 2010)
The aim of this study was to evaluate the effect of different levels of rapeseed expeller cake (RC) in the diet of laying hens on egg performance, egg quality, retention and excretion of nitrogen, calcium and phosphorus, and metabolizability of energy. The experiment was carried out with 72 Bovans Brown hens, from 28 to 53 weeks of age. Experimental treatment consisted of four isonitrogenous and isocaloric corn-soybean diets (as calculated: 17% crude protein, 11.6 MJ/kg metabolizable energy, 0.81% lysine, 0.36% methionine, 3.60% calcium and 0.37% available phosphorus), containing 0, 4, 6 or 8% RC. The RC used was produced from double zero rapeseed and contained 29.3% crude protein, 17.4% crude fat, 10.8% crude fibre, 0.63% calcium, 0.97% phosphorus, 1.91% lysine and 0.84% methionine. During the experimental period, the dietary level of RC had no significant effects on egg performance and egg quality parameters. Boiled eggs from hens fed a diet with 8% RC were characterized by an inferior flavour to those from other groups. There were no treatment effects on nitrogen balance or metabolizability of energy, though the highest dietary level of RC negatively affected retention and excretion of calcium and phosphorus.
Keywords: rapeseed expeller cake; laying hens; egg quality; nutrient retention